A Rare Extraskeletal Osteosarcoma Appearing After 55 Years on a Large Stage 3 Burn Scar - O. Vanhooteghem; I. Theate (Case Reports in Dermatological Medicine)
It is widely accepted that chronic burn wounds may lead to the development of various malignant skin tumors. Deep stage 3 burned areas may facilitate deeper carcinogenesis. Deep tissues are probably less subject to severe insult than is the epithelial layer during physical insult, suggesting that soft tissues transform to a lesser extent during the late stages of tumoral development as in an immunocompromised district with altered local immune defense with both cellular and humoral defense affected. Most authors claim that tumors are almost squamous cell carcinomas, although other types of malignancies such as basal cell carcinoma and, to a lesser extent, melanoma can also be seen. However, malignant transformation of cutaneous soft tissue in a burn insult area has rarely been described. Similarly, burn-induced tumors of histiocytic origin have been reported in few cases and osteosarcoma only in two case reports. Here, we report a patient case suffering from severe large stage 3 burn after-effects on the leg. Fifty-five years after the injury, this patient developed a large extraosseous osteosarcoma on the scar.